Soil microbial community structure, metabolic potentials and influencing factors in a subtropical mountain forest ecosystem of China. Issue 1 (1st January 2020) - Zhao, Rudong; Yang, Xiaolu; Tian, Qiuxiang; Wang, Xinggang; Liao, Chang; Li, Cheng-Liang; Liu, Feng
ABSTRACT: This study investigated the variances in soil microbial community (SMC) structure and metabolic potentials in subtropical mountain forest ecosystem. Soil samples (0–10, 10–30 and 30–60 cm) were collected within 27 plots (20×20 m 2 ) that were randomly assigned. Changes in SMC structure were mainly regulated by soil physicochemical property and tree diversity in 0–10 cm depth, by total nitrogen (TN) and clay in 10–30 cm depth, and by soil organic carbon (SOC) and pH in 30–60 cm depth. Metabolic potential variance was mainly driven by soil chemical property in 0–10 cm depth, by SOC and TN in 10–30 cm depth, and by TN in 30–60 cm depth. Collectively, soil physicochemical properties were the primary factors influencing SMC structure and its metabolic potentials along the soil profile, but the expected effects of tree diversity and topography were not evident.